Radiological Study of Fusion of Tri-radiate Cartilage in hip bone in Bikaner Region in 14-22 Years Age Group (Indian Journal of Forensic Medicine & Toxicology, 2020)
Correct age determination has of great importance in legal prosecution. The principle means, which enableone to form fairly accurate opinion about age of an individual, are general physical development, dentition,secondary sex characters and ossification of bones. Among them Radiological examination of ossificationprocess is most accurate than any other method up to 25 years of age.This study involves radiological examination of Pelvis (AP view) of 169 individuals for the study of agerelated appearance and fusion of ossification center of Tri-radiate cartilage in hip in the individuals of agegroup of 14-22 years of both male and female in S P Medical college, Bikaner, Rajasthan.